Ex situ cultivation of the endangered savin junipers (Juniperus sabina L.) from the Western Carpathians - Jadwiszczak, Katarzyna; Parzonko, Sylwia; Mazur, Małgorzata; Marcysiak, Katarzyna; Boratyński, Adam; Bona, Agnieszka (Biodiversity: Research and Conservation, 2024)
Ex situ conservation methods provide immediate insurance against extinction of relict trees and shrubs in the wild. To be well-managed, the living collection should be well-studied in respect of the place of origin of the individuals, their taxonomic status, and genetic variation. Using 12 nuclear microsatellite loci, we analysed 22 shrubs of Juniperus sabina L. var. sabina (savin juniper), cultivated in the Kórnik Arboretum (Poland) and sourced from a Tertiary relict population in the Pieniny Mts. (Western Carpathians). We found 2 clonal pairs of individuals and a pair of full siblings. The genetic diversity parameters were rather low: NA = 2.5 alleles per locus, HO = 0.316, HE = 0.326, and the inbreeding coefficient was also very low (GIS = 0.03). The individuals formed 3 groups in the principal coordinates analysis (PCoA), but 2 of these groups were genetically close. The Bayesian clustering analysis revealed that the specimens belonged to 2 genetic groups. We recommend that the cultivation of J. sabina var. sabina should be carefully protected, as it represents remnants of the Tertiary genetic diversity of the species.